Faktor Internal dan Eksternal Yang Mempengaruhi Pembiayaan Murabahah Pada Perbankan Syariah di Indonesia - Azmi, Fika (Graduasi: Jurnal Bisnis & Ekonomi, 2015)
his  research aims to examine  internal  and  external  factors that  influence Murabaha  Financing  on  Islamic  banking  In  Indonesia.  This  research  used  five independent  variables, that  is Deposit Third  Party  Fund, Non Performing  Financing, Murabaha  Margin,  Inflation  and Bank  Indonesia  Certificates  Sharia  (SBIS).  The population  in this  research  are  all Islamic  banks, Islamic  Business Unit (UUS), and Sharia Rural Banks (BPRS) in Indonesia. The sample consisted of three banks that are determined  by purposive sampling technique. The criteria  used that foreign Islamic bank that  issued quarterly financial  statements in  the  year 2010-2014. The  hypothesis was  tested  using multiple  regression  analysis. The  results  of this  research  shows  that Deposit Third  Party Fund  and Murabaha  Margin have  asignificant positive effect on Murabaha  Financing.  While  the  Non  Performing  Financing,  Inflation  and  Bank Indonesia Certificates Sharia have no significant effect on Murabaha Financing